2014
DOI: 10.1016/j.scr.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac stem cell niches

Abstract: The critical role that stem cell niches have in cardiac homeostasis and myocardial repair following injury is the focus of this review. Cardiac niches represent specialized microdomains where the quiescent and activated state of resident stem cells is regulated. Alterations in niche function with aging and cardiac diseases result in abnormal sites of cardiomyogenesis and inadequate myocyte formation. The relevance of Notch 1 signaling, gap-junction formation, HIF-1α and metabolic state in the regulation of ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 100 publications
(139 reference statements)
0
57
0
Order By: Relevance
“…Satellite cells of the skeletal muscle are located along muscle fibers, between the basement membrane and the sarcolemma [28]. Whereas cardiac progenitors have been identified in the heart, the specific niche localization remains elusive [53]. However, it has been reported that the myocardium possesses interstitial structures with the architectural organization of stem cell niches that harbor cardiac progenitors [54].…”
Section: Diversity Of the Stem Cell Nichementioning
confidence: 99%
“…Satellite cells of the skeletal muscle are located along muscle fibers, between the basement membrane and the sarcolemma [28]. Whereas cardiac progenitors have been identified in the heart, the specific niche localization remains elusive [53]. However, it has been reported that the myocardium possesses interstitial structures with the architectural organization of stem cell niches that harbor cardiac progenitors [54].…”
Section: Diversity Of the Stem Cell Nichementioning
confidence: 99%
“…However, cardiac niches are not limited to the subepicardium and are dispersed throughout the myocardium (328). CPC niches are more numerous in the atria and apex, which represent protected anatomical areas characterized by low hemodynamic stress (44,117,120,141,198,280,327,328). The process of myocyte formation lacks directionality; the scattered distribution of the sites of cardiomyogenesis complicates the demonstration of the topography of cardiac niches.…”
Section: Cpc Nichesmentioning
confidence: 99%
“…Until the research of Anversa and Nadal-Ginard (Anversa and Nadal-Ginard, 2002) was published, it was thought that cardiomyocytes in adults do not have the ability to divide. Later studies have shown that regeneration of the cardiac muscle is more intense in ischemic heart failure (Urbanek et al, 2005, Doppler et al, 2013, and that cardiac stem cells (CSC) which are able to differentiate into all structural components of the heart exist (Barile et al, 2007Leri et al, 2014.…”
Section: Heart -Biological Backgroundmentioning
confidence: 99%